Comparative Effectiveness and Safety of Early Enteral Feeding Versus Total Parenteral Nutrition in Postoperative Recovery Following Major Abdominal Surgery A Meta-Analysis of Clinical Outcomes and Complications - Ejaz, Sonia; Khan, Muhammad Hakimullah; Akbar, Aima; Khan, Uzair; Khan, Ali Zaman; Akbar, Siddiq; Muhammad Waqas; Qaseem, Omair (Indus Journal of Bioscience Research, 2025)
This meta-analysis investigates the comparative effectiveness and safety of early enteral feeding (EEN) versus total parenteral nutrition (TPN) in postoperative recovery following major abdominal surgeries, including gastrointestinal resections, esophagectomies, and cystectomies. A systematic review of 12 studies, including randomized controlled trials (RCTs), systematic reviews, and secondary analyses published from 2014 to 2024, was conducted. The primary outcomes analyzed were hospital stay duration, complication rates, and nutritional status, while secondary outcomes included gastrointestinal recovery, immune function, and cost-effectiveness. The results revealed that EEN significantly outperformed TPN in several key areas. EEN was associated with a shorter hospital stay (mean reduction of 2.1 days), fewer infectious complications (risk ratio [RR] 0.68), and reduced pulmonary complications (RR 0.60). Nutritionally, patients in the EEN group exhibited improved outcomes, including higher serum albumin levels (mean difference 0.42 g/dL) and less weight loss (-1.1 kg) compared to those receiving TPN. Additionally, EEN promoted faster gastrointestinal recovery (mean difference of -1.4 days) and improved immune function. Subgroup analyses highlighted the particular advantages of EEN in gastrointestinal and gastric cancer surgeries, where it facilitated quicker recovery and fewer complications. There were no significant differences in mortality rates between the two feeding strategies. Sensitivity and heterogeneity assessments confirmed the robustness of the findings, although moderate risk of bias was observed in some studies. This meta-analysis supports the use of EEN over TPN in postoperative nutritional support, offering better clinical outcomes, faster recovery, and fewer complications, making it a more effective and cost-efficient approach in major abdominal surgeries.